Zeolite-Based Materials for the Catalytic Oxidation of VOCs: A Mini Review - Xue, Tianshan; Yang, Li (Frontiers in Chemistry, 2021)
Catalysts for VOCs combustion have been widely studied and zeolite-based materials have been structured to meet the need of particle use in this area. This review summarized several new trends in zeolite-based catalysts for VOCs cataleptic oxidation. Intensive efforts have been devoted to the optimization of composition and structure of catalysts, abatement of CVOCs, design of zeolite-based monolithic catalysts and adsorbent/catalyst bi-functional material. The suggestions for further work was put forward based on the collation of recently published papers.